The effects of daily step goals of 10, 000, 12, 500, and 15, 000 steps per day on neural activity to food cues: A 24‐week dose‐response randomized trial. Issue 5 (16th April 2022) - Compton, Sharla E.; Larson, Michael J.; LeCheminant, James D.; Tucker, Larry A.; Bailey, Bruce W.
Abstract: Introduction: The purpose of this study was to examine the effect of different levels of sustained physical activity on neural reflections of attention allocated toward food cues in first year college women. Methods: Seventy‐nine first‐year college women (18.6 ± 0.5 years) were recruited to participate in the study. Women were randomly assigned to a daily step goal of 10, 000, 12, 500, or 15, 000 for 24 weeks. Once during weeks 16–24, participants were shown pictures of plated meals or flowers with the neural response measured using the P300 and late positive potential (LPP) components of the scalp‐recorded event‐related potential. Diet was assessed using the automated 24‐h recall. Results: Both the P300 and LPP amplitudes were significantly more positive to food versus flower pictures ( p s < .001). There was no interaction between step group and picture condition for the P300 and LPP. However, the 12, 500‐step group showed a significantly elevated LPP amplitude in comparison to the other groups for both food and flowers ( F (2, 74) = 8.84; p < .001). The effect size for the combined results (food and flowers) was 0.56 between 10, 000 and 12, 500‐step groups, and 0.75 between the 12, 500‐ and 15, 000‐step groups. In addition, the 12, 500 group reduced caloric consumption over the course of the intervention ( t (1, 74) = 3.35, p = .001, dz = 0.59). Conclusion: Habitual physical activity of 10, 000, 12, 500, or 15, 000 steps per day does not preferentially alter neural reflections toward food cues compared to flowers. There may be a nonlinear response to pleasant visual cues, with 12, 500 steps per day eliciting higher LPPs than either 10, 000 or 15, 000. Abstract : The purpose of this study was to examine the effect of different levels of sustained physical activity on neural reflections of attention allocated toward food cues in first year college women. Habitual physical activity of 10, 000, 12, 500, or 15, 000 steps per day does not preferentially alter neural reflections toward food cues compared to flowers. There may be a nonlinear response to pleasant visual cues, with 12, 500 steps per day eliciting higher LPPs than either 10, 000 or 15, 000.